Implementation of Assimilation of Criminals in The Time of The Covid-19 Pandemic: A Study in The Legal Area of Class IIA Prisons in Banda Aceh - Nurhafifah Nurhafifah; Teuku Irvan Riyadi (Syiah Kuala Law Journal, 2021)
The Decree of the Minister of Law and Human Rights Number M.HH-19.PK.01.04.04 of 2020 concerning the Release and Release of Prisoners and Children Through Assimilation and Integration in the Context of Prevention and Control of the Spread of Covid-19 stated that the provision of assimilation was given to reduce the prevention of Covid-19 However, in the implementation of the assimilation of prisoners at the Class IIA prison in Banda Aceh, it is still not running optimally due to increasing public concerns and unrest amid economic difficulties as a result of the Covid-19 pandemic. In an effort to provide assimilation of inmates with the Assessment and Supervision system of officers to assimilation prisoners at the Class IIA Banda Aceh Prison, the prisoners must behave well, as evidenced by not undergoing disciplinary punishment within the last 6 months.